2017
DOI: 10.23937/2469-5823/1510084
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Simulation among Undergraduate Students in the Critical Care Nursing

Abstract: IntroductionNovice nursing students are trained to develop skills for delivering safe patient-centered holistic care in the undergraduate nursing. Entry of novice students in the higher levels of the undergraduate curriculum entails their adult clinical experience in the intensive care, high acuity, post-anesthetic and emergency settings. This clinical practice exposes the students to a variety of clinical conditions with unpredictable socio-cultural and psychosocial background [1]. With growing patient acuity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The use of simulation videos, however, played a role as a mediocre replacement to in-person simulation activities. Interactivity is an essential component of healthcare simulation (18) and passively watching simulation videos without interactivity does not satisfy the standards of best practice for healthcare simulation (19). To resolve this issue, we developed an Interactive Video Simulation (IVS) software that converts a simulation video into an interactive experience using educators' existing video content.…”
Section: Introductionmentioning
confidence: 99%
“…The use of simulation videos, however, played a role as a mediocre replacement to in-person simulation activities. Interactivity is an essential component of healthcare simulation (18) and passively watching simulation videos without interactivity does not satisfy the standards of best practice for healthcare simulation (19). To resolve this issue, we developed an Interactive Video Simulation (IVS) software that converts a simulation video into an interactive experience using educators' existing video content.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Teaching presence is the design, facilitation, and direction of cognitive and social processes to realize personally meaningful and educationally worthwhile learning outcomes. [6] Cognitive presence is the extent to which learners can construct and confirm meaning through sustained reflection and discourse. [6] The process of community inquiry can facilitate an understanding of the complexities of building student relationships.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Cognitive presence is the extent to which learners can construct and confirm meaning through sustained reflection and discourse. [6] The process of community inquiry can facilitate an understanding of the complexities of building student relationships.…”
Section: Introductionmentioning
confidence: 99%
“…A positive sign indicates the better the learning process is applied; the students will feel more satisfied. In research conducted by D'souza et al (2017) on 100 nursing, students showed a significant relationship between the simulation learning process and student satisfaction (p = 0.03) [25]. Thus, the simulation learning process directly increases student satisfaction and student knowledge and performance related to critical care and nursing care compared to students only learning by watching videos.…”
Section: Discussionmentioning
confidence: 92%